Laju Dekomposisi Serasah di Lahan Mangrove Rehabilitasi - Destiana Destiana; Herlina Darwati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the rate of decomposition and the nutrient content of carbon (C-org), nitrogen (N) and phosphorus (P) of mangrove leaf litter released during the decomposition process. The method used is purposive sampling, where the determination of observation stations is based on the year of mangrove planting, namely 2007, 2010, 2013 and 2016. The analysis of litter decomposition rate uses the Boonruang equation, C-org uses the Walkley & Black method, N uses the Kjeldahl method and P uses the wet destruction method. The results showed that the most significant decomposition rate occurred in the 2016 planting year litter of 71.924%, followed by 2007, 2010 and 2013 planting years with a value of 58,582%, 55,360% and 47,048%, respectively. The highest nutrient content of C-org and P was found in mangroves in the 2010 planting year with values ​​of 50.82 and 0.14 ppm, and the highest N nutrient content was in the 2007 planting year with a value of 1.25%. In conclusion, the mangrove leaf litter during the research was not completely decomposed. The decomposition process in the 2010 planting year had the highest C-org and P-released nutrients. The highest N nutrient content was found in the 2007 planting year. Keywords: Decomposition Rate, Mangrove, Litter